Mechanical Analysis of Subgrades of Road Pavements in Life Cycle Assessment - Marina Donato; Bruno Guida Gouveia; Alexandre Simas de Medeiros; Marcelino Aurélio Vieira da Silva; Sandra Oda (Salehan Institute of Higher Education, 2022)
When evaluating the sustainability of a construction project, it is important to verify the influence of climate uncertainty and the depletion of natural resources that permeate the strategies to make infrastructure possible, especially those associated with the transportation sector, which have great potential to generate environmental impacts. Thus, the objective of this study is to evaluate the effect that subgrade material variation, which constitutes highway pavements with flexible surfacing, can generate in the Life Cycle Assessment (LCA) of these infrastructures. For this purpose, pavements that had the same materials and thicknesses for the execution of the base (gravel soil-NG') and the subbase (clay soil LG'), but with subgrades composed of different types of tropical soils, classified as lateritic and non-lateritic, were proposed. The combination of these elements enabled the elaboration of pavements with different service lives and atmospheric emissions. The scope of the study included the phases of extraction and production of the inputs necessary to build the roadway envisioned in each scenario, as well as the construction phase itself, considering the operation of construction equipment. The LCA focused on the emission of greenhouse gases (GHGs) and the quantity of primary energy employed in the phases considered. It was concluded that the materials used in this study have similar mechanical behavior, and therefore the results of the design of the thicknesses of the asphalt overlay were close and consequently result in similar energy consumption and greenhouse gas emissions. Doi: 10.28991/CEJ-2022-08-07-012 Full Text: PDF